2021
DOI: 10.15587/2706-5448.2021.239437
|View full text |Cite
|
Sign up to set email alerts
|

Development of a method for maintaining the performance of drilling fluids during transportation by Platform Supply Vessel

Abstract: The object of research is the process of transportation of drilling fluid used for lubrication and cooling of drilling equipment of offshore oil production platforms. The subject of the study is the stratification of the density of the drilling fluid along the height of the cargo tank in which it is transported. The technology of transportation of drilling fluid on the Platform Supply Vessel is considered. A problematic point in ensuring this process is that during the transportation of drilling fluids, due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The sedimentation stability of the drilling slurry was calculated by expression (1), its values for different transportation methods are given in Table 2.…”
Section: Research Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sedimentation stability of the drilling slurry was calculated by expression (1), its values for different transportation methods are given in Table 2.…”
Section: Research Resultsmentioning
confidence: 99%
“…A set of previous studies on the study of the rheological characteristics of drilling slurries established the occurrence of stratification of its density along the depth of the tank. In this case, due to the stratification of the drilling slurry, the difference in its density on the surface and bottom of the tank can reach 40 % [1,10]. As a way to reduce the density stratification of the drilling slurry, it is possible to use additional circulation of the slurry between the tanks (Fig.…”
Section: Methods Of Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…On sea and river ships, steam turbine, gas turbine and diesel plants are used as heat engines. At the same time, diesel engines are installed on all ships without exception, regardless of their type, class and deadweight [1,2]. The effective power of diesel engines is used to propel the ship or provide electrical energy to ship equipment, mechanisms and systems.…”
Section: Introductionmentioning
confidence: 99%
“…In studies [7,8], it was found that when drilling fluids are transported by PSV class vessels to offshore oil platforms, a latent stratification of drilling fluids occurs along the depth of the cargo tank. The consequence of this is a decrease in the sedimentation stability of the drilling fluid and the formation in the bottom of the cargo tank of sediment from heavy components with which it is alloyed.…”
Section: Introductionmentioning
confidence: 99%